Save the cat! writes a young adult novel : the ultimate guide to writing a YA bestseller - Brody, Jessica (Ten Speed Press, 2023)
"An indispensable guide in the bestselling Save the Cat! story structure series that reveals the 15 essential plot points needed to make any young adult novel a success, from an accomplished novelist and the author of Save the Cat! Writes a Novel"--Provided by publisher.